Peran Komunitas Pencinta Alam Dalam Menjaga Kelestarian Lingkungan Di Kabupaten Pangkajene Dan Kepulauan - Mr. Aswandi; Darman Manda (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2023)
The purpose of this study was to find out: (1) The role of the nature lover community in Pangkajene and Archipelago districts in preserving the environment amid rampant environmental damage. (2) the impact of the role of the nature lover community in Pangkajene and Islands districts in preserving the environment amid rampant environmental damage. To achieve this goal, the researchers used data collection techniques through observation, interviews and documentation. The data obtained from the research results were processed using qualitative descriptive analysis in a phenomenological paradigm on the role of the nature-loving community in Pangkajene and Islands Regency in preserving the environment in the midst of widespread environmental damage. Based on the results of this study indicate that; (1) There are four roles of the nature lover community in Pangkajene and Kepulauan Regency in preserving the environment amid rampant environmental damage, namely public education, clean action, saving energy, and planting trees. (2) the impact of the role of the nature lover community in Pangkajene and Islands Regencies in preserving the environment in the midst of widespread environmental damage can have a good impact, namely increasing concern for caring for and protecting nature, avoiding global warming, protecting ecosystems.